Evaluación del Servicio de Ayuda a Domicilio en Alcorcón: diagnóstico para la mejora de la calidad del servicio - ROBLES RÍOS, Paz; LARA MARTÍNEZ, Francisco (Cuadernos de Trabajo Social, 2009)
The rapid development of the culture of Quality Management in Public Administration will reestablish a new way of thinking distant from what currently exists about what can be demanded of public services. Evaluation as an undeniably integrated practice within planning and operating management is now linked with the democratic principles of responsibility, transparency and participation. The demand for social services and attention rises as Social Services become universal and diversify and the issues they address become more urgent. For any municipality, Home Health Assistance Service is probably the most relevant social resource because of the issues it addresses as well as the budgetary impact it has. This article presents the experience of the City Government of Alcorcon in the evaluation of this in-home service within the context of continuous improvement since its inception.
Keywords: Home health assistance; Municipalities; Evaluation; Diagnosis; Quality; Applied research; Methodological triangulation